Pengaruh Kepuasan Merek dan Kepercayaan Merek terhadap Loyalitas Merek pada Perusahaan Leasing Sepeda Motor di Kota Surakarta - Kusuma, Dhori Pridana, Dr. Anton Agus Setyawan, SE, MM (2016)
This study aims to determine of brand satisfaction and brand trust to brand loyalty on motorcycle leasing company in Surakarta, either partially or simultaneously. The population in this study are individuals who have ever used the services of motorcycle leasing company in the city of Surakarta. The sample in this study amounted to 150 people with the determination of the sample using purposive sampling technique. Data obtained primary data questionnaire with likert scale. Data were analyzed using multiple linear regression, t-test, F-test, and coefficient of determination. The result show : (1) brand satisfaction and brand trust significant effect on brand loyalty. (2) F test result obtained F arithmetic value of 67.978 with sig. 0,000 so simultaneously there is the influence of brand satisfaction and brand trust to brand loyalty. (3) The test results obtained value of R Square of 0.473 thus concluced variation changes in brand loyalty can be explained brand satisfaction and brand trust of 47.3% while the remaining 52.7% is explained by other variables outside variables examined in this study.